Oxidative addition of dihydrogen to divanadium in solid Ne: multiple-donded triplet HVVH and Singlet V2(μ-H)2 - Hübner, Olaf; Himmel, Hans-Jörg (Angewandte Chemie. International edition, 2020)
Dinuclear compounds of early transition metals with a high metal-metal bond order are of fundamental interest due to their intriguing bonding situation and of practical interest because of their potential involvement in catalytic processes. In this work, two isomers of V2H2 have been generated in solid Ne by the reaction between V2 and H2 and detected by infrared spectroscopy: the linear HVVH molecule (3Σg− ground state), which is the product of the spin-allowed reaction between V2 (3Σg− ground state) and H2, and a lower-energy, folded V2(μ-H)2 isomer (1A1 ground state) with two bridging hydrogen atoms. Both isomers are characterized by metal-metal bonding with a high bond order; the orbital occupations point to quadruple bonding. Irradiation with ultraviolet light induces the transformation of linear HVVH to folded V2(μ-H)2, whereas irradiation with visible light initiates the reverse reaction.
First published: 14 April 2020
Im Titel ist "2" bei "V" und bei (μ-H) tiefgestellt
Gesehen am 10.11.2021